Transcutaneous spinal DC stimulation reduces pain sensitivity in humans - Meyer-Frießem, Christine; Magerl, Walter (Neuroscience letters, 2015)
Non-invasive approaches to pain management are needed to manage patient pain escalation and to providing sufficient pain relief. Here, we evaluate the potential of transcutaneous spinal direct current stimulation (tsDCS) to modulate pain sensitivity to electrical stimuli and mechanical pinpricks in 24 healthy subjects in a sham-controlled, single-blind study. Pain ratings to mechanical pinpricks and electrical stimuli were recorded prior to and at three time points (0, 30, and 60min) following 15min of anodal tsDCS (2.5mA, “active” electrode centered over the T11 spinous process, return electrode on the left posterior shoulder). Pain ratings to the pinpricks of the highest forces tested (128, 256, 512mN) were reduced at 30min and 60min following anodal tsDCS. These findings demonstrate that pain sensitivity in healthy subjects can be suppressed by anodal tsDCS and suggest that tsDCS may provide a non-invasive tool to manage mechanically-induced pain.